The Influence of Age, Sex, and BMI on Neck Cartilage and Bone Fractures in Hanging Deaths: A 6-Year Autopsy Study - Bork, T.; Sehlikoglu, K.; Celbis, O.; Oner, B. S. (Wolters Kluwer Medknow Publications, 2025)
Background:Asphyxia by hanging is caused by the constricting force of a ligature encircling the neck, with gravity pulling the body downward. Postmortem examinations should focus on cartilaginous and soft tissues in the neck region.Aim:The present study aims to demonstrate the effect of various variables such as age, sex, height, weight, and BMI on postmortem findings in cartilaginous and bone tissues in the neck region.Materials and Methods:The study is a retrospective descriptive study covering 248 cases of death by hanging.Results:The mean age of the cases was 39.8 years, and 69.8% (n = 173) of the cases were male. Thyroid cartilage fracture was observed in 98 (39.5%) cases and hyoid bone fracture in 80 (33.3%) cases. Hyoid bone fractures were 4.4 times more frequent in women (P < 0.05). Although there was no significant difference between the number of thyroid cartilage fractures and sex (P = 0.274). There was a significant difference in terms of weight (P = 0.004) in cases with thyroid fracture and in weight (P = 0.001) and height (P = 0.037) in cases with hyoid fracture. A significant difference was observed in BMI in the occurrence of thyroid cartilage fractures (P < 0.05).Conclusion:This study is one of the largest series in the literature and is an important study that reveals the statistical significance of neck cartilage and bone tissues in autopsy results. When investigating neck cartilage and bone fractures in cases of death by hanging, the attending physician should consider the physical condition of the individual.
Keywords: Asphyxia death; hanging; neck injuries; suicide